Community perceptions of the existence of mangrove ecosystems in Peunaga Cut Ujong Village, Meureubo District - Nurul Najmi; Rahmawati Rahmawati; Eka Lisdayanti (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Local communities played an important part of thepi existence of the mangrove ecosystem in Peunaga Cut ujong Village. Community perspectives on the existence of mangrove ecosystems have an impact on mangrove management steps in the local area. The purpose of this study was to identify community perceptions of the existence of mangrove ecosystems around the Peunaga Cut Ujong Village community. This research uses survey methods and in-depth interviews using a questionnaire sheet as a guide. The technique of determining respondents through snowball sampling. Respondents totaled 35 people who were selected based on the area of residence of the youth hamlet of Peunaga Cut Ujong Village. Data analysis of this research used Likert scale. The results showed that community perceptions of the functions and benefits of mangrove ecosystems had the lowest score of 858, the form of management score 916, and the level of participation with a score of 1246. Overall, the perceptions and opinions of local communities about the existence of mangrove ecosystems are in the very good category, with a score of 127. This value shows that the existence of mangroves is very good in the view of the Peunaga Cut Ujong community. Community involvement in mangrove conservation efforts will actually have an impact on the success of sustainable management.